2022
DOI: 10.1186/s12967-022-03700-4
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the moderating effects and repercussion of exercise intervention on osteoporosis: ingenious involvement of gut microbiota and its metabolites

Abstract: Osteoporosis (OP) is a systemic bone disease characterized by the decreased bone mass and destruction of bone microstructure, which tends to result in the enhanced bone fragility and related fractures, as well as high disability rate and mortality. Exercise is one of the most common, reliable and cost-effective interventions for the prevention and treatment of OP currently, and numerous studies have revealed the close association between gut microbiota (GM) and bone metabolism recently. Moreover, exercise can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 155 publications
0
7
0
Order By: Relevance
“…With the continuous advancement of the aging process of global population, the number of middle‐aged and elderly people around the world has increased dramatically (Zhang, Cao, Li, Chen, Yu, & Rui, 2022 ; Zhang, Lu, Li, Dai, Chen, et al, 2021 ), causing an increasingly heavy social burden caused by osteoporosis and osteoporosis‐related fragile fractures (Watts et al, 2021 ; Zhang, Lu, Li, Wang, Zhao, Chen, & Rui, 2022 ). Meanwhile, several previous studies have reported the disorder of gut microbiota in patients with osteoporosis and OVX‐induced osteoporosis mice models, indicating that there is an inseparable relationship between gut microbiota and bone metabolism (Li et al, 2021 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the continuous advancement of the aging process of global population, the number of middle‐aged and elderly people around the world has increased dramatically (Zhang, Cao, Li, Chen, Yu, & Rui, 2022 ; Zhang, Lu, Li, Dai, Chen, et al, 2021 ), causing an increasingly heavy social burden caused by osteoporosis and osteoporosis‐related fragile fractures (Watts et al, 2021 ; Zhang, Lu, Li, Wang, Zhao, Chen, & Rui, 2022 ). Meanwhile, several previous studies have reported the disorder of gut microbiota in patients with osteoporosis and OVX‐induced osteoporosis mice models, indicating that there is an inseparable relationship between gut microbiota and bone metabolism (Li et al, 2021 ; Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the increasingly severe aging process of the global population, the problem of osteoporosis faced by the elderly has become increasingly prominent (Zhang et al, 2022 ). Osteoporosis is a systemic and metabolic bone system disease characterized by low bone mass, destruction of bone microstructure, increased bone fragility, and enhanced fracture risk (Eastell & Szulc, 2017 ; Zhang, Cao, Li, Chen, Yu, & Rui, 2022 ; Zhang, Cao, Li, Zhang, Wu, Yu, & Rui, 2022 ). According to previous studies, more than 200 million people worldwide suffer from osteoporosis, and an osteoporotic fracture occurs every 3 s (Qiu et al, 2022 ; Tao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, the concept and studies of gut-bone axis have been gradually developed and deepened. In the previous works, our research group also reviewed and summarized the regulatory effects and significance of GM and its metabolites on OP [12], as well as the regulatory effects of exercise [15], and probiotics, prebiotics [17] on GM and OP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the abundance and diversity of GM may gradually decrease with advancement of age [14], with a dysbiotic pattern increasing harmful bacteria, while decreasing the number of beneficial bacteria. Several studies in recent years have also indicated that there are certain differences between the GM of patients with OP and healthy individuals, and the severity of bone loss in human body is also closely related to the alterations of GM [15,16], which to some extent reveals that GM might be a potential target for the prevention and treatment of OP.…”
Section: Introductionmentioning
confidence: 99%
“…Immune cells play a crucial role in the bone tissue microenvironment [ 56 58 ]. Studies have shown that resident macrophages are present in all tissues, with exception of hyaline cartilage [ 59 ] and are intimately involved in tissue repair, debris removal, and maintaining the microenvironment homeostasis [ 60 ].…”
Section: Microenvironmental Characteristics Of Opmentioning
confidence: 99%